Report on the conclusions and recommendaitons (Interaction Council New YorkUS, 1993)
Focuses on action that would have to be taken in order to turn Africa around viz. the political development of countries and regions within the continent; economic development across the continent; means of engaging the international community; short-term measures including those which address acute issues of survival of Africa societies. Looks at the situation in South Africa.
Chairman: Lord Callaghan of Cardiff